Corroborating the equivalence between the Duffin-Kemmer-Petiau and the Klein-Gordon and Proca equations - Castro, L. B.; De Castro, A. S. [UNESP] (American Physical Society (APS), 2014)
It is shown that the Hamiltonian version of the Duffin-Kemmer-Petiau theory with electromagnetic coupling brings about a source term at the current. It is also shown that such a source term disappears from the scenario if one uses the correct physical form for the Duffin-Kemmer-Petiau field, regardless of the choice for representing the Duffin-Kemmer-Petiau matrices. This result is used to fix the ambiguity in the electromagnetic coupling in the Duffin-Kemmer-Petiau theory. Moreover, some widespread misconceptions about the Hermiticity in the Duffin-Kemmer-Petiau theory are discussed. © 2014 American Physical Society.